2015
DOI: 10.1177/0022034515583999
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Network Underlying Hypodontia

Abstract: Mammalian tooth development is a precise and complicated procedure. Several signaling pathways, such as nuclear factor (NF)-κB and WNT, are key regulators of tooth development. Any disturbance of these signaling pathways can potentially affect or block normal tooth development, and presently, there are more than 150 syndromes and 80 genes known to be related to tooth agenesis. Clarifying the interaction and crosstalk among these genes will provide important information regarding the mechanisms underlying missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 58 publications
1
127
0
Order By: Relevance
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 56%
“…individuals with hypodontia were mandibular second premolars, followed by maxillary lateral incisors, as reported in a recent meta-analysis, 33 it is likely that there is an overlapping phenotype in some of the individuals with WNT10A and WNT10B mutations. The selective pattern in WNT10B mutants is also different from that of mutations in other oligodontia-associated genes, such as MSX1 (missing second premolar) and PAX9 (agenesis of molars), as described previously 7,10,11,34 and currently in the individuals with the p.Ile97Leufs*217 variant ( Figure S1). Regardless, protein-protein-interaction and genetic studies have shown crosstalk between PAX9 and the Wnt pathway (e.g., AXIN2) or MSX1 in dental tissues, 11 which are essential for the establishment of the odontogenic potential of the mesenchyme.…”
mentioning
confidence: 68%
“…The selective pattern in WNT10B mutants is also different from that of mutations in other oligodontia-associated genes, such as MSX1 (missing second premolar) and PAX9 (agenesis of molars), as described previously 7,10,11,34 and currently in the individuals with the p.Ile97Leufs*217 variant ( Figure S1). Regardless, protein-protein-interaction and genetic studies have shown crosstalk between PAX9 and the Wnt pathway (e.g., AXIN2) or MSX1 in dental tissues, 11 which are essential for the establishment of the odontogenic potential of the mesenchyme. However, the underlying mechanism of different genotype-phenotype correlations observed here remains elusive.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Our understanding of the genetics underlying tooth agenesis has progressed greatly in recent years, with approximately 80 genes found to be related to tooth agenesis [3]. However, OMIM lists 111 different syndromes associated with oligodontia.…”
Section: Introductionmentioning
confidence: 99%